THE SEMIOTICS OF TEXTUAL THRESHOLDS OF " ANA WA ANTE" COLLECTION BY AHMAD ELKHAME - السَّيد نجوان كمال (Tobruk University Journal of Social and Human Sciences, 2023)
This research paper aims to study the textual thresholds in the story collection " Ana wa Ante " by the writer Dr. / Ahmed Al-Khamisi. Textual thresholds are an essential component in understanding the specificity of the literary text, deciphering its mysteries, defining its semantic intentions, interpreting it, and illuminating its mysterious aspects I noticed that he was often interested in forming the titles of his short story collection . It did not come in an absurd manner in vain, but it was closely associated with the text, until it became a major and inseparable part of it, It is noticeable that the nominal addressing has significantly outperformed the actual address. It was mentioned in fourteen stories, The actual address is only found in his story entitled: "I will open the door and see you." The writer was interested in textual transcendence in his collection, especially gifting, naturalization, and internal addresses.